Papel dos receptores canabinóides em um modelo experimental de angiogênese inflamatória - Rodrigo Guabiraba Brito (2007)
Angiogenesis depends on a complex network of cells and mediators. The activation or blockade of cannabinoid receptors showed to be an interesting pharmacological strategy to attenuate the angiogenic and/or inflammatory response in many experimental models. Here we investigated how this strategy may interfere in inflammatory angiogenesis. Polyester-polyurethane sponges were implanted in C57BL/6 mice. Animals received daily doses (10 mg/kg, s.c.) of the cannabinoid antagonists SR141716A (CB1) and SR144528 (CB2), separately, or 3 and 10 mg/Kg (30 or 100 ìg/mice, for the local treatment) (s.c.) of the cannabinoid CB1/CB2 agonist WIN 55212-2, for 7 or 14 days. The implants were then collected for ELISA, hemoglobin, myeloperoxidase and N-acetylglucosaminidase measurements, used as indexes for angiogenesis, neutrophil and macrophage accumulation, respectively. Histological analysis was also conducted. CB1 or CB2 receptor antagonist treatment was able to reduce cellular influx to the sponge at 7 and 14 days, with distinctive pattern for macrophages and neutrophils. The CB1/CB2 agonist also reduced cellular influx. Both treatments affected angiogenesis. These alterations were accompanied by changes in the levels of TNF-á, VEGF, CXCL1-3/KC, CCL2/JE and RANTES, depending on the treatment. All changes correspond to a similar pattern in the histological analysis. The blockade or activation of cannabinoid receptors showed to be effective in reducing inflammatory and angiogenic responses. Altough acting in a similar way, levels of cytokines, chemokines and endocannabinoids may help explain this paradoxal response. Partial agonism / inverse agonism activity and receptor desensitization is another explanation for these responses.Keywords: angiogenesis, inflammation, cannabinoid receptors, cytokines